2010
DOI: 10.1021/jp103014b
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Individual Proton Affinities of Ofloxacin from its UV−Vis Absorption, Fluorescence and Charge-Transfer Spectra: Effect of Inclusion in β-Cyclodextrin on the Proton Affinities

Abstract: Individual proton affinities of the four dissociable functional groups of (+/-)-9-fluoro-2,3-dihydro-3-methyl-10-(4-methyl-1-piperazinyl)-7-oxo-7H-pyrido[1,2,3-de]-1,4-benzoxazine-6-carboxylic acid (commonly called "ofloxacin" and to be denoted henceforth as OflH), have been determined from the pH-dependent variation of the UV-vis absorption and fluorescence spectra of the compound itself and of its charge transfer complexes (CT) with p-bromanil and p-chloranil (in aqueous medium containing 0.1% ethanol, v/v).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Deep insertion of guest molecules inside the host results in strong van der Waals effects, a process characterized by negative enthalpy changes and negative entropy changes. Similar results were experimentally obtained for the inclusion complex formation of OFL with bCD [49]. It was reported that the complexation was associated with an enthalpy change, DH, of -30.5 kcal mol -1 and an entropy change, DS, of -87.2 J mol -1 K -1 .…”
Section: Molecular Modelingsupporting
confidence: 88%
“…Deep insertion of guest molecules inside the host results in strong van der Waals effects, a process characterized by negative enthalpy changes and negative entropy changes. Similar results were experimentally obtained for the inclusion complex formation of OFL with bCD [49]. It was reported that the complexation was associated with an enthalpy change, DH, of -30.5 kcal mol -1 and an entropy change, DS, of -87.2 J mol -1 K -1 .…”
Section: Molecular Modelingsupporting
confidence: 88%
“…Whereas the study of acid-base equilibrium of 4-nitrophenol show that 4-nitrophenolate (the negatively charged basic form) has more affinity than the acidic (neutral) form. It has been claimed that the driving force of more stable inclusion complex of 4-nitrophenolate with β-CyD is the hydrogen bonding [17,18].…”
Section: Uv Vis Spectral Changesmentioning
confidence: 99%
“…Indeed, this effect was already reported with other dyes systems, capable of interacting with CD molecules. In particular, it was demonstrated that, as the result of inclusion complex formation, the guest molecule is surrounded by the hydrophobic microenvironment of the CD cavity. This environmental change causes some modification of the chemical and physical properties of the guest molecule, such as equilibria and kinetic parameters and absorption coefficient. As an example, it was found that upon binding of phenolphthalein to β-CD cavity in aqueous solution at pH 10.5, the red-colored dianion form is rapidly transformed into a colorless lactonoid form .…”
Section: Resultsmentioning
confidence: 99%